A Theoretic Extension and Empirical investigation of conducting Business Online Social Network: The Continuance Intention Phenomenon - Assensoh-Kodua, Akwesi (Journal of Economics and Behavioral Studies, 2014)
Online Social Network (OSN) is a web 2.0 enabled technology that permits OSN participants to interact with both old and new friends initially. This model of OSN ventured into conducting business activities on platforms, which resulted in many springing up but not surviving, yet the explosion of business activities on these platforms continuous to grow. It is therefore important that OSN practitioners and researchers understand the key determinants of OSN business transaction and continuance intention propellants. The purpose of this paper is to establish the factors that determine OSN participant’s continuance intention to do business on OSN platform. The research framework is grounded in an extended expectation-confirmation model (ECM). An online survey model was used to collect 300 valid responses from OSN participants who have ever conducted business using OSN. A partial least square version 2.0.M3 (PLS) and Warp PLS 4.0 were deployed to perform CFA analyses and structural equation modelling, respectively. The emerging results provide significant evidence in support of the five out of nine factors tested against the hypotheses proposed, namely: Perceived Behavioural Control (0.01), Satisfaction (0.14), Expected Benefit (0.15), Social Norms (0.24), and Habit (0.31), as the main determinants of OSN continuance intention.